An approach to using the AQI components in urban air pollution sources identifying - Prokhorova, Svitlana (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Problem statement. The fact that the air we breathe is polluted is well known. There are many sources of pollution, especially in big cities. Various sensors are installed to monitor pollutants in the air. One of the global systems for registering the concentration of pollutants in urban air is AQI. Air quality monitors collect data of five major air pollutants – ground-level ozone, particle pollution, carbon monoxide, sulfur dioxide, and nitrogen dioxide, that then convert to the Air Quality Index. And although the sensors themselves are not capable of reducing pollution in the air, based on the data they provide, it is possible to create indicative maps of urban pollution. Such mapping of urban areas will enable authorities to develop and implement plans to improve the most dangerous areas, as is already done in other countries. But there are still no such maps for Kyiv.Study objective is to analyse the air quality index in Kyiv, identify the main source of atmospheric pollution and to visualize urban air pollution.Methodology involves data analysis from 15 sensors of the AQI worldwide network. We analyzed the concentration of 5 main air pollutants contributed to the common Air Quality Index for a certain period in Kyiv and its surroundings. Knowing the exact coordinates of each sensor and the results of their measurements, we drew a map of air pollution in Kyiv using OriginPro 8.1 software and images from the Google maps.Research results. It was determined that the largest contribution to the Air Quality Index is made by the fine particulate matter emissions. We determined that the morning sensor data on the amount of dust in the air is the most informative. It is known transportation is one of the main sources of PM2.5 in the city. Our map clearly shows that the area with the highest AQI value coincides with a major road junction on the north-west outskirts of the city. Thus, atmospheric pollution in Kyiv is mainly determined by the amount of fine dust in the air. Further research will be aimed at identifying the relationship between the amount of PM2.5 in the air and the morphological parameters of indicator plants.Scientific novelty of the research. We showed for the first time that air pollution does not coincide with the official sources of atmospheric pollution given by the Kyiv Bureau of Technical Supervision. We also presented new approach to draw up-to-date, representative, and accurate pollution maps that can be submitted to the representatives of environmental services and other interested parties. Such investigations are of great importance as they can give the opportunity to the government to take real actions on pollutants reducing.